Exploring the effectiveness of functional training in preventing shoulder injuries among young Chinese tennis players from educational and social psychological perspectives - Pengju Xie; Nur Shakila Mazalan; Denise Koh Choon Lian (Environment and Social Psychology, 2025)
Objective: From the perspectives of education and social psychology, this study systematically investigated the effectiveness of functional training on shoulder injury prevention among young Chinese tennis players and its underlying mechanisms. Methods: The study employed a mixed-methods research design, recruiting 88 tennis players aged 14-18 as participants, who were randomly assigned to either the experimental group or the control group (44 participants each). The experimental group received a 16-week comprehensive functional training intervention program that integrated multiple elements including health education, peer support, and coach support, while the control group maintained their regular training routine. The study systematically assessed physiological indicators such as injury incidence rate, shoulder function scores, and athletic performance, as well as psychosocial indicators including injury prevention knowledge, self-efficacy, health behavior attitudes, peer influence, and coach relationship quality at four time points: baseline, mid-intervention, post-intervention, and follow-up. Results: Compared to the control group, the experimental group’s injury incidence rate decreased significantly from 43.2% at baseline to 9.1% at the end of the intervention (p<0.001), with notable improvements in shoulder function and athletic performance. At the psychological-cognitive level, the experimental group demonstrated a 56.7% increase in injury prevention knowledge, a 48.4% enhancement in self-efficacy, a 50.1% improvement in preventive behavioral intention, and ultimately achieved an 89.6% preventive behavior execution rate. Further moderation analysis revealed that peer support (β=0.38, p<0.001) and coach relationship quality (β=0.42, p<0.001) exerted significant positive moderating effects on the preventive effectiveness of functional training. Conclusion: This study confirms that functional training can significantly enhance shoulder injury prevention effectiveness through a synergistic three-level mechanism of "physiological improvement-psychological reinforcement-social support." Educational factors (knowledge enhancement and self-efficacy improvement) play a crucial mediating role in training effectiveness, while psychosocial factors (peer support and coach relationships) exert important moderating effects on prevention outcomes. The research findings validate the theoretical value and practical significance of a multidisciplinary integrated perspective in the field of sports injury prevention, providing empirical evidence for constructing a scientific and humanized injury prevention system.